2020
DOI: 10.1186/s13063-020-04536-3
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of chest compression cycle length and real-time feedback with a CPRmeter® on chest compression quality in out-of-hospital cardiac arrest: study protocol for a multicenter randomized controlled factorial plan trial

Abstract: Background: With a survival rate of 6 to 11%, out-of-hospital cardiac arrest (OHCA) remains a healthcare challenge with room for improvement in morbidity and mortality. The guidelines emphasize the highest possible quality of cardiopulmonary resuscitation (CPR) and chest compressions (CC). It is essential to minimize CC interruptions, and therefore increase the chest compression fraction (CCF), as this is an independent factor for survival. Survival is significantly and positively correlated with the suitabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…QCPR Classroom was found to help students obtain high-quality CPR training, especially in terms of correct compression depth and full recoil [ 44 ]. Other research studying the influence of received feedback on CPR quality [ 45 , 46 ] reported similar conclusions.…”
Section: Discussionsupporting
confidence: 62%
“…QCPR Classroom was found to help students obtain high-quality CPR training, especially in terms of correct compression depth and full recoil [ 44 ]. Other research studying the influence of received feedback on CPR quality [ 45 , 46 ] reported similar conclusions.…”
Section: Discussionsupporting
confidence: 62%
“…QCPR Classroom was found to help students obtain high-quality CPR training, especially on correct compression depth and full recoil [35]. Other research studying the in uence of received feedback on CPR quality [36][37] have reported similar conclusions.…”
Section: Discussionmentioning
confidence: 63%
“…It is worth emphasizing, that the use of TrueCPR feedback device resulted in an increase in the depth of compressions compared to the group where CPR was conducted without CPR feedback device. Also, other studies where CPR was conducted without the use of PPE-AGP suits show that CPR feedback devices improve both the depth and frequency of chest compressions [19][20][21][22].…”
Section: Discussionmentioning
confidence: 96%